International migratory agreements: The paradox of adverse interest - José Antonio Alonso; Francisco Javier Santos Arteaga (IZA Journal of Development and Migration, 2020)
This article seeks to explain the contradiction between the promises of welfare gains derived from the economic models recommending the removal of immigration restrictions and the realities experienced by countries attempting to apply restrictions to immigration flows. A formal model is built in which the strategic reaction of countries considers not only the benefits derived from migration but also the (economic and non-economic) costs that migration can generate in the host country. Strategic reactions drive what may be called the "paradox of adverse interest": the fewer potential gains associated with liberalization of migration, the easier it becomes for nations to reach an unrestrictive agreement. The existence of two asymmetries (between the bargaining power of receiving and sending countries, and between the private nature of most of migration's benefits and the social nature of its main costs) can hinder the agreement when the countries involved exhibit a high wage differential. Results suggest that permissive international agreements on migration are easier to reach in regional contexts, among countries with proximate economic conditions and levels of income.
Keywords: J61; J68; J82; 330; international migration; unskilled and skilled migration; adverse interest; factor endowments; asymmetric migration effects; migratory agreements